ACS: an alternate coding scheme to improve degrade read performance for SSD-based RAID5 systems. (20th November 2021) - Pan, Yubiao; Lin, Mingwei
To guarantee high performance and reliability, storage systems require better devices and data redundancy schemes, e.g., SSD-based RAID5. However, failures in the large-scale storage systems are common. In order to serve requests on a failed node, the SSD-based RAID5 causes additional disk I/Os to trigger degraded reads. Existing coding methods are not suitable for the SSD-based RAID5. How to maintain the same storage cost as the traditional RAID5 does while obtaining less disk I/Os for degraded reads is an interesting problem. In this paper, we first come up with an alternate coding scheme (ACS) by using the characteristics of SSD to reduce disk I/Os for boosting degraded reads. To work for realistic workloads, we further propose ACS-W and ACS-DR approaches for write and degraded requests. Our evaluations based on the trace-driven simulator with real-world workloads show that ACS indeed reduces disk I/Os and improves the degraded read performance.